2016
DOI: 10.4103/2277-9175.192735
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of liquid-based cytology with conventional Papanicolaou smears in cervical dysplasia diagnosis

Abstract: Background:Due to the high number of women affected by cervical cancer and the importance of an early diagnosis, combined with the frequent incidence of false-negative Papanicolaou (Pap) smear screening results for this disease, several studies have been conducted in recent years in order to find better tests. Liquid-based cytology (LBC) tests, including the liquid-based thin layer method, have demonstrated the highest potential for reducing false-negative cases and improved sample quality. This study aimed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 34 publications
0
17
0
2
Order By: Relevance
“…Inadequate samples were observed in 0.3% of LBC samples versus 0.7% of Pap smears (P =.002) [32] in another study. There were 0.1% and 1.7% inadequate smear cases in the LBC method and CP, respectively, in the Tuncer et al study [33,34,35]. In the Kirschner et al study, inadequate cases were 2.3% and 0.3% in the LBC and CP respectively [36].…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Inadequate samples were observed in 0.3% of LBC samples versus 0.7% of Pap smears (P =.002) [32] in another study. There were 0.1% and 1.7% inadequate smear cases in the LBC method and CP, respectively, in the Tuncer et al study [33,34,35]. In the Kirschner et al study, inadequate cases were 2.3% and 0.3% in the LBC and CP respectively [36].…”
Section: Discussionmentioning
confidence: 88%
“…The results of Yousefi et al showed that inadequate cases were 1 case (0.3%) with CP and 14 cases (1%) wi th the LBC method [35].…”
Section: Discussionmentioning
confidence: 98%
“…In fact, many researches have been conducted to evaluate and compare the efficacy of LBC with CPS as a screening tool for cervical cancer. Results lead to the conclusion that LBC samples provide higher quality samples by offering better clarity and uniform spread of smears, which reduces the number of unsatisfactory cases and requires less time for screening [18,19,20]. This has even more impact in postmenopausal women, where menopause-induced anatomical and hormonal changes make screening particularly challenging [19].…”
Section: Cervical Cancer Screening Characterizationmentioning
confidence: 99%
“…2 More recently, this technique has been modified into a liquid-based Pap smear or liquid-based cytology (LBC) to improve early detection, reduce false-negative rates, and simplify quality control (QC) that is demanded by conventional cervical cytology. 3 These modifications also offer advantages extending to multiple slide preparation, the incorporation of special stains (immunohistochemistry), human papillomavirus (HPV) detection through DNA testing, 1 and even the potential to detect other gynecological malignancies, most notably, endometrial and ovarian cancers. 4,5…”
Section: Introductionmentioning
confidence: 99%